An Efficient One-Pot Strategy for the Synthesis of Triazole-Fused 1,4-Benzodiazepinones from N-Substituted 2-Azidobenzamides - Majumdar, K. C.; Ganai, Sintu (Synthesis, 2013)
A catalyst-free, one-pot strategy for the synthesis of 1,2,3-triazole-fused 1,4-benzodiazepinone derivatives from N-substituted 2-azidobenzamides and propargyl bromide, in the presence of a base, is reported. The products are formed in good to excellent yields via N-alkylation followed by a 1,3-dipolar cycloaddition.
Keywords: fused triazole; azide–alkyne cycloaddition; 1,4-benzodiazepinones; N-substituted 2-azidobenzamides; catalyst-free